A Child with Acute Encephalopathy Associated with Quadruple Viral Infection - Nakata, Keiko; Kashiwagi, Mitsuru; Masuda, Midori; Shigehara, Seiji; Oba, Chizu; Murata, Shinya; Kase, Tetsuo; Komano, Jun A. (Frontiers in Pediatrics, 2015)
Pediatric acute encephalopathy (AE) was sometimes attributed to virus infection. However, viral infection does not always result in AE. The risk factors for developing infantile AE upon virus infection remain to be determined. Here, we report an infant with AE co-infected with human herpesvirus-6 (HHV-6) and three picornaviruses, including coxsackievirus A6 (CVA6), Enterovirus D68 (EV-D68), and human parechovirus (HPeV). EV-D68 was vertically transmitted to the infant from his mother. CVA6 and HPeV were likely transmitted to the infant at the nursery school. HHV-6 might be re-activated in the patient. It remained undetermined, which pathogen played the central role in the AE pathogenesis. However, active, simultaneous infection of four viruses should have evoked the cytokine storm, leading to the pathogenesis of AE. Conclusion: an infant case with active quadruple infection of potentially AE-causing viruses was seldom reported partly because systematic nucleic acid-based laboratory tests on picornaviruses were not common. We propose that simultaneous viral infection may serve as a risk factor for the development of AE.